Cash grants to manufacturers after Cyclone Idai: RCT evidence from Mozambique - Hanna Berkel; Peter Simonsen Fisker; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In March 2019, Cyclone Idai hit central Mozambique and caused widespread damage, including businesses in the enterprise sector. We use panel data and a randomized controlled trial to estimate the impact of unconditional cash grants on micro enterprises and their recovery. We find that, on average, the cash grants had a positive effect on firm revenue, profits and savings, and the likelihood of having their roof repaired. The cash had a stronger impact in the more damaged city (Beira) compared to the less affected location (Chimoio) and was particularly effective for carpenters. These findings indicate that access to finance is critically important for firm recovery following disasters.
Keywords: O12; O14; Q54; H81; 330; firms; manufacturing; natural disasters; cyclone; unconditional cash grants; randomized controlled trial